2016
DOI: 10.1002/bab.1484
|View full text |Cite
|
Sign up to set email alerts
|

Efficient kinetic resolution of (RS)‐1‐phenylethanol by a mycelium‐bound lipase from a wild‐type Aspergillus oryzae strain

Abstract: A mycelium-bound lipase from Aspergillus oryzae (AOL) exhibited excellent enantioselectivity for kinetic resolution of (RS)-1-phenylethanol ((RS)-1-PE) in organic solvent. The various reaction parameters affecting the conversion and enantioselectivity were studied, including type of acyl donor, solvent, molar ratio, temperature, enzyme amount, and substrate concentration. The optimum reaction conditions were found to be transesterification with vinyl acetate at 30 °C in methyl tert-butyl ether with a vinyl ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The optimal temperature was lower than that of the native lipase (Yan et al 2017). Wu et al also discovered that the LSC displayed a lower optimal temperature than the native one (Wu et al 2004).…”
Section: Effect Of Reaction Temperature On Lsc-catalyzed Resolution Of (Rs)-1-pementioning
confidence: 80%
See 2 more Smart Citations
“…The optimal temperature was lower than that of the native lipase (Yan et al 2017). Wu et al also discovered that the LSC displayed a lower optimal temperature than the native one (Wu et al 2004).…”
Section: Effect Of Reaction Temperature On Lsc-catalyzed Resolution Of (Rs)-1-pementioning
confidence: 80%
“…The LSC prepared with tetrahydrofuran (THF) as a cosolvent exhibited the highest activity in resolution of (RS)-1-PE, giving a conversion of 46.8% with a reaction time of 2 h. The activity of the LSC was significantly higher than that of natural lipase (myceliumbound lipase). The natural lipase required about 24 h to achieve the same conversion rate (Yan et al 2017). The LSC prepared without an organic cosolvent likewise displayed a higher conversion of 31.6% with the same reaction time (at 2 h of reaction).…”
Section: Effect Of Organic Cosolvent On the Preparation Of Lscmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true for older patients with significantly declined body functions that result in high sensitivity and poor tolerance to hypoxia. It was confirmed that ( 3 , 4 ) both spontaneous respiration and the heartbeat can be restored in some older patients with cardiac and respiratory arrest, if it is detected early, and treated immediately and appropriately. Early detection and immediate and appropriate treatment can reduce the impact of respiratory and cardiac arrest on the functions of key organs, and is therefore the key to a successful rescue.…”
Section: Introductionmentioning
confidence: 82%